Diet-Induced Obesity Alters the Circadian Expression of Clock Genes in Mouse Gustatory Papillae - Bernard, Arnaud; Dastugue, Aurélie; Maquart, Guillaume; Delhaye, Stéphane; Duez, Hélène; Besnard, Philippe (Frontiers in Physiology, 2020)
Diet-induced obesity (DIO) is associated with a defect of the orosensory detection of dietary lipids in rodents. This dysfunction is not anecdotic since it might worsen the negative effects of obesity by promoting the overconsumption of energy-dense foods. Previous studies have highlighted a progressive devaluation of reward value of lipid stimuli due to a desensitization of dopaminergic brain areas in DIO mice. Paradoxically, the putative deleterious impact of obesity on peripheral fat detection by the gustatory papillae remains poorly documented. Using a whole transcriptomic investigation of the circumvallate papillae (CVP), an analysis of CVP genes involved in fat taste transduction and signaling along the day, and two bottle choice tests, we have found that i) CVP, known to house the most taste buds in the oral cavity, displays a circadian rhythmicity, ii) DIO reduces the oscillation of key genes involved both in the circadian clock and lipid detection/signaling, and iii) the gene invalidation of the clock gene Rev-Erbα does not significantly affect fat preference despite an oily solution intake slightly lower than littermate controls. Taken together these data bring the first demonstration that the gustatory function is under control of a peripheral clock in mammals, as already reported in fly and suggest that a disturbance of this rhythmicity might contribute to the lower fatty taste acuity found in obese mice.